Thin, very thin, or ultrathin-strut biodegradable or durable polymer-coated drug-eluting stents. (November 2020) - Buiten, Rosaly A.; Zocca, Paolo; von Birgelen, Clemens
Abstract : Purpose of review: The current article will review recently published clinical studies that evaluate very thin or ultrathin-strut drug-eluting stents (DES), focusing on major randomized clinical trials in broad patient populations. Recent findings: Multiple randomized trials recently assessed the clinical performance of novel very thin to ultrathin-strut DES. Most randomized trials established noninferiority of the novel device. To date, only one major randomized clinical trial (i.e., BIOFLOW V) showed superiority of an ultrathin-strut biodegradable polymer-coated sirolimus-eluting stent over a very thin-strut durable polymer-coated everolimus-eluting stent in a relatively broad patient population. There are signals that the same ultrathin-strut biodegradable polymer-coated sirolimus-eluting stent may improve clinical outcome in specific patient populations. For example, in the randomized BIOSTEMI trial, 1-year superiority of the ultrathin-strut DES was found in patients presenting with an acute ST-segment elevation myocardial infarction. Yet, substudies of large randomized trials that assessed patients with small-vessel treatment showed equivocal results. Summary: Although two randomized trials showed advantages for ultrathin-strut DES, other clinical trials provided no significant evidence that ultrathin-strut DES improve clinical outcome. The question whether ultrathin-strut DES may reduce the repeat revascularization risk following implantation in small vessels is a matter of further debate and future research.